Insulin Topical Application for Wound Healing in Nondiabetic Patients - Shudong Sun (Hindawi Limited, 2021)
Background. Low-cost and safe strategies to improve wound healing will be of great social and economic value. The goal of this pilot clinical trial is aimed at analyzing how effective insulin therapy is at healing wounds in nondiabetic people. Methods. In this protocol research, 346 individuals were included. Patients were divided as 2 groups at random: experimental patients were given a ten-unit answer. For each 10 cm2 of wound, insulin was injected in solution with 1 mL 0.9 percent saline, whereas the control group got a standard dressing with normal saline. Results. During the therapy period, no adverse effects were reported. After insulin therapy, no substantial insulin-related side effects were reduced. After 10 days of therapy, the experimental group’s granulation tissue coverage rate and thickness were considerably improved as compared to control. Furthermore, a momentous difference in the occurrence of wound bleeding and suppurative wounds between the two groups (P=0.05). Conclusion. The results of this pilot research suggest that insulin injections could harmless and effective alternative therapy for wound healing in nondiabetic individuals and that larger, placebo-controlled trials are needed to evaluate effectiveness and safety of insulin treatment in wound healing patients.